Determination of Punicalagins Content, Metal Chelating, and Antioxidant Properties of Edible Pomegranate (Punica granatum L) Peels and Seeds Grown in Morocco - Talal Sabraoui; Taleb Khider; Boubker Nasser; Rabiaa Eddoha; Abderrahman Moujahid; Maryam Benbachir; Abdelkhalid Essamadi (International Journal of Food Science)
Pomegranate (Punica granatum L) is widely cultivated in the Mediterranean countries especially in Morocco. Pomegranate peel and seed contain considerable amounts of phenolic compounds with antioxidant activity. The aim of the present study was to phytochemically characterize the pomegranate peels and seeds obtained from three Moroccan provinces, using UHPLC-DAD. In addition, total phenolic content (TPC), total flavonoid contents (TFC), and metal chelating of pomegranate peel were also evaluated. The results showed that pomegranate peel possesses the highest phenolic (TPC: 224.39 mg GAE/g dw) and flavonoid (TFC: 62.64 mg rutin/g dw) contents. Punicalagin-β and punicalagin-α, are the abundant compounds found in peel: 216.36±9.94 mg/g, 154.94±5.21 mg/g, respectively. Pomegranate peels showed significantly (p<0.05) high antioxidant activity 1-diphenyl-2-picrylhydrazyl (DPPH) EC50: 42.71±0.04 μg/mL, 2.2′-Azino-bis(3-Ethylbenzothiazoline-6-Sulfonic Acid) (ABTS) EC50: 62.15±0.01 μg/mL), and chelating activity (FRAP 1.85±0.00 mg ascorbic acid equivalents/100 g, Fe2+: 2.52±0.01 μmol EDTA equivalents/g dw) compared to seeds. A positive correlation between antioxidant activity and total phenolic was found. According to achieved results, high antioxidant capacity of pomegranate extracts, especially peel, shed light to further use as natural food preservatives. Pomegranate peel could be used for the fortification of food with fiber by introducing it in dietary, as well as in health applications due to its higher antioxidant capacity.